Knee osteoarthritis and bone marrow aspirate as a treatment choice – Narrative review (Research, Society and Development, 2021)
Introduction: Osteoarthritis (OA) is the leading cause of pain and physical disability in the world, in addition to being related to more than 100 rheumatological and orthopedic conditions that affect the joints and their tissues. Objective: Compile, in portuguese, information on the use of boné marrow aspirate in the treatmen of knee OA. Methods: Narrative review conducted through literary and scientific sources, through the platform US National Library of Medicine (PUBMED). The Health Science Descriptors used were: knee osteoarthritis, epidemiology, etiology, pathophysiology, treatment, bone marrow aspirate. Discussion: OA has mechanisms that cause inflammation to some degree in chondrocytes and synovial cells, releasing some cytokines, that decrease collagen synthesis and stimulate catabolic madiators, causing apoptosis to chondrocytes. Thus, bone marrow aspirate (BMA) emerges as an interesting cell therapy, since its mesenchymal stem cells (MSC), has a great immunomodulatory potential, although its mechanisms are not yet fully understood. Conclusion: new therapeutic options, such as MSC obtained by BMA, appear to supply the spaces left by the most used treatments today, due to their immunomodulatory interaction. Certainly, there are still gaps in its mechanisms, requiring more studies on the topic, in order to consolidate it as a totally viable treatment for OA, as can be conclused from the promising existing studies.